2022
DOI: 10.34172/japid.2022.017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an herbal mouthwash on periodontal indices in patients with plaque-induced gingivitis: A cross-over clinical trial

Abstract: Background. Recent advances in alternative medicine have led to the introduction of various new herbal products for treating gingivitis as the most prevalent gingival disease. The present study clinically evaluated the effect of a herbal mouthwash consisting of 5 herbal extracts (Myrtus communis, Quercus brantii, Punica granatum, Portulaca olerace, and Boswellia serrata) on periodontal indices. Methods. Fifty patients with plaque-induced gingivitis were included in this randomized, dou­ble-blinded clinical tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Several studies describe clinical trials using frankincense extracts to treat several conditions, such as knee pain [59,60], hepatic inflammation and lipid metabolism [61], and chronic low back pain [62]. Regarding oral health, three publications report the effects of B. serrata extracts in the treatment of periodontitis [63][64][65]. Ardakani et al showed that patients using a mouthwash consisting of five herbal extracts (including B. serrata extracts) improved their periodontal condition in plaque-induced gingivitis comparable to the effect of 0.2% chlorhexidine mouthwash [63].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies describe clinical trials using frankincense extracts to treat several conditions, such as knee pain [59,60], hepatic inflammation and lipid metabolism [61], and chronic low back pain [62]. Regarding oral health, three publications report the effects of B. serrata extracts in the treatment of periodontitis [63][64][65]. Ardakani et al showed that patients using a mouthwash consisting of five herbal extracts (including B. serrata extracts) improved their periodontal condition in plaque-induced gingivitis comparable to the effect of 0.2% chlorhexidine mouthwash [63].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding oral health, three publications report the effects of B. serrata extracts in the treatment of periodontitis [63][64][65]. Ardakani et al showed that patients using a mouthwash consisting of five herbal extracts (including B. serrata extracts) improved their periodontal condition in plaque-induced gingivitis comparable to the effect of 0.2% chlorhexidine mouthwash [63]. However, because the authors used a mix of five natural products, it is not possible to conclude whether B. serrata extracts play a role in the improvement of clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Measures such as GI, PI and PD play a fundamental role in the assessment of gum health. These indices provide information about the reality and prevalence of gum disease and are important in the development of treatment plans [ 37 ]. It was observed that these measurements were higher in the case group compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Chamomile mouthwashes are even comparable to scaling and root planning or the use of 0.2% chlorhexidine in the treatment of periodontitis. 8,9 Porphyromonas gingivalis is a major player in the pathogenesis of periodontal disease. We have evaluated the antimicrobial activity of chamomile tea on P. gingivalis in vitro.…”
Section: Dear Editormentioning
confidence: 99%
“…6,7 Chamomile mouthwashes are even comparable to scaling and root planning or the use of 0.2% chlorhexidine in the treatment of periodontitis. 8,9…”
mentioning
confidence: 99%